Keefektifan Model Pembelajaran Addie Berbantuan Media Miniatur Bangun Datar terhadap Prestasi Belajar Matematika Siswa Kelas II pada Mi Negeri 3 Banyumas - Nurlaely Nurlaely; Rizki Fitrianto (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The development of science and technology that is not balanced with facilities, infrastructure and teacher skills in teaching in schools has caused a decline in mathematics learning achievement of grade II students from year to year. Although this problem has been improved, it has not been resolved. So another solution was made by using the ADDIE model assisted by miniature flat shape media. The problem is, is there a difference in learning achievement using the ADDIE model assisted by miniature flat shape media with learning achievement using the conventional model? The research design was a pretest-posttest control group design. The instruments used were achievement tests and student learning activity observation sheets. The data analysis technique in this study used an initial analysis using a normality test and a test of equality of two means and a final analysis using a normality test and a t-test. The result was that the initial analysis of the two samples was normal and the average was the same. While the final analysis of the two normal samples and the t-test stated that t count = 4.036> t table = 2.025 so that there was a difference in the average mathematics learning achievement of those who received instruction using the ADDIE model assisted by miniature flat shape media with those who used the conventional model.